SERS and DFT study of p-hydroxybenzoic acid adsorbed on colloidal silver particles - Chen, Y; Chen, S J; Li, S; Wei, J J (Cellular and Molecular Biology, 2015)
In this study, normal Raman spectra of p-hydroxybenzoic acid (PHBA) powder and its surface-enhanced Raman scattering (SERS) spectra in silver colloidal solutions were measured under near infrared excitation conditions. In theoretical calculation, two models of PHBA adsorbed on the surfaces of silver nanoparticles were established. The Raman frequencies of these two models using density functional theory (DFT) method were calculated, and compared with the experimental results. It was found that the calculated Raman frequencies were in good agreement with experimental values, which indicates that there are two enhanced mechanism physical (electromagnetic, EM) enhancement and chemical (charge-transfer, CT) enhancement, in silver colloidal solutions regarding SERS effect. Furthermore, from high-quality SERS spectrum of PHBA obtained in silver colloids, we inferred that PHBA molecules in silver colloids adsorb onto the metal surfaces through carboxyl at a perpendicular orientation. The combination of SERS spectra and DFT calculation is thus useful for studies of the adsorption-orientation of a molecule on a metal colloid.